Navigating collaborative learning across national boundaries: a comparative study of educators’ perspectives in Israel and Turkey - Pothou, Eleni; Eliyahu-Levi, Dolly; Sonbahar, Begüm; Ganz-Meishar, Michal (Frontiers in Human Dynamics, 2024)
The primary goal of the KIDS4ALLL project was to empower educators to foster a flexible, innovative, and collaborative learning environment within their classrooms. This article delves into teachers' experiences with implementing collaborative learning during the KIDS4ALLL project. Additionally, it explores how teachers perceived the implementation of the KIDS4ALLL pilot in learning environments across different national educational settings, specifically in Israel and Turkey. Given that both Israel and Turkey have centralized education systems and adhere to a traditional teaching approach, the two research questions offer insights into how the national education context of both countries influences the implementation of the collaborative learning approach of KIDS4ALLL and the experiences of educators. The findings highlight a sense of fear and uncertainty among educators regarding their ability to conduct lessons in an unfamiliar yet innovative and flexible learning environment. These feelings were accompanied by challenges such as technological and language barriers, socio-cultural diversities, and occasional behavioral issues. The results also underscore similarities between the two countries, emphasizing that centralized education systems, teachers' previous training, curriculum, and available physical space posed challenges to the pilot program's implementation.